CEREBRAL HEMODYNAMICS IN PATIENTS WITH HYPERTENSION COMBINED WITH ERYTHROCYTOSIS - Nataliia M. Ovodiuk; Andriy Ya. Bazylevych (Клінічна та профілактична медицина, 2025)
Introduction. Cerebrovascular diseases, which include acute forms (such as stroke and transient ischemic attack) and chronic forms (such as discirculatory encephalopathy), are among the most significant medical and social problems both in our country and worldwide due to their high prevalence and severe consequences. One of the causes of chronic brain ischemia can be the disturbance of blood rheological properties, specifically its thickening. Erythrocytosis is one such factor.